PENGARUH POLA PENGGERGAJIAN TERHADAP RENDEMEN DAN WAKTU MENGGERGAJI KAYU MERANTI (SHOREA SPP.) *) - Osly Rachman; Sadan Widarmana; Surjono Surjokusumo (Jurnal Penelitian Hasil Hutan, 1988)
The  effects  of sawing pattern on recovery  and sawing   time   was studied  using  72 logs of meranti  (Shorea spp.).  The logs were divided  into  4 grades  i.e., Prime, First,  Second  and Local, each group consisting of 18 logs.  Each group  was sawn with  3  different  sawing  patterns,    namely semi  quarter, round  and  live  sawing. In  the sawing pattern study the  effect of logs  diameter, brittle heart, and sapwood  on recovery were  also observed.The  results  indicated  that  semi  quarter,  round,  and  live sawing patterns  generated  a  recovery  as much  as 46,37  %, 43,48  % and  37,61 %,  respectively. The  recovery  of Prime  grade  logs was 46,92 % which  was  not  significantly  different from  that of the First grade logs.  The  Second  grade logs produced  a recovery  of 37.12 % and was not significantly different from  that  obtained  from Lokal grade  logs. The sawing rate  was highest  when  live sawing  pattern  was applied, i.e.,  0.92  m3/ hour.